Repeated sprint ability and stride kinematics are altered following an official match in national-level basketball players - Delextrat, A.; Baliqi, F.; Clarke, N. (The Journal of Sports Medicine and Physical Fitness, 2013)
Aim: The aim of the study was to investigate the effects of playing an official national-level basketball match on repeated sprint ability (RSA) and stride kinematics. Methods: Nine male starting basketball players (22.8±2.2 years old, 191.3±5.8 cm, 88±10.3 kg, 12.3±4.6% body fat) volunteered to take part. Six repetitions of maximal 4-s sprints were performed on a non-motorised treadmill, separated by 21-s of passive recovery, before and immediately after playing an official match. Fluid loss, playing time, and the frequencies of the main match activities were recorded. The peak, mean, and performance decrement for average and maximal speed, acceleration, power, vertical and horizontal forces, and stride parameters were calculated over the six sprints. Differences between pre- and post-match were assessed by student t-tests. Results: Significant differences between pre- and post-tests were observed in mean speed (-3.3%), peak and mean horizontal forces (-4.3% and -17.4%), peak and mean vertical forces (-3.4% and -3.7%), contact time (+7.3%), stride duration (+4.6%) and stride frequency (-4.0%), (PConclusion: These results highlight that the impairment in repeated sprint ability depends on the specific activities performed, and that replacing fluid loss through sweating during a match is crucial.